Library markers space in academic and public library (2020)
This study examines the Library Markers Space in Academic and Public libraries. These spaces are specifically designed, aimed at meeting the unexpressed needs of library users and to influence them to profitably engage in the library by creating physical or digital objects, which are open for the free use of all library users. Library’ makerspace enables Graphic arts, web design and animation and assists students in their projects that involve digital images. Nevertheless, factors such as lack of technical skills, inadequate power supply and lack of trained manpower distort the application of Library Markers Space in academic and public libraries